HIRARKI NILAI DALAM CERITA RAKYAT BHUJU’ TOLOMBHUNG DI DESA BATOKABAN - Slamet; Resdianto Permata Rahardjo; Darni (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2026)
The folklore of Bhuju’ Tolombhung in Bangkalan represents a unique local knowledge system, characterizing a sacred site as a natural saltwater spring phenomenon rather than a gravesite. This study aims to deconstruct the spiritual value structure within the narrative using Notonagoro's axiology analysis. Employing a qualitative descriptive approach with observation and in-depth interview data collection techniques involving custodians and community leaders of Batokaban Village, the research of Hierarchy of Values in the Folk Story of Bhuju’ Tolombhung in Batokaban Village reveals four integrative value dimensions. The value of truth appears as cosmological logic positioning the site as Axis Mundi; the value of goodness manifests in taboo ethics serving as ecological conservation; the value of beauty is reflected through agrarian symbolism of the "granary stone"; and the value of religiosity teaches the essence of monotheism through asceticism myths. The interesting facts found in this research prove that the Bhuju’ concept is flexible as a personification of living nature, affirming the function of folklore as a cultural defense mechanism and moral guide for the Madurese community.